ANALISIS YURIDIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 135/PUU-XXI/2024 TENTANG PERUBAHAN DESAIN KONSTITUSIONAL KESERENTAKAN PEMILU DI INDONESIA - Taufik; Ayu Mega Sukma; Elviandri (Collegium Studiosum Journal, 2025)
The Indonesian Constitutional Court Decision Number 135/PUU-XXI/2024 marks a fundamental change in Indonesia's constitutional and electoral law system by annulling the application of the full concurrent elections concept which combines the National General Election (Pemilu) and the Regional Head Election (Pilkada)—as regulated in Law Number 7 of 2017 concerning General Elections. The Court determined that the unification of national and local election schedules contradicts the principle of regional autonomy (otonomi daerah) and blurs the meaning of popular sovereignty at the local level as guaranteed by Article 18 of the 1945 Constitution (UUD 1945). Through this ruling, the Court ordered that Pilkada must be held separately from the national Pemilu, issuing a conditionally constitutional verdict that reinterprets Article 201 of the Election Law to prevent a legal vacuum (rechtsvacuum). This research utilizes a normative juridical approach with descriptive and conceptual analysis methods, through a review of relevant laws and regulations, Constitutional Court decisions, and academic literature. The analysis results indicate that the Court’s considerations encompass three main dimensions: (1) Philosophical, relating to the protection of popular sovereignty in the regions; (2) Sociological, concerning the workload of election organizers and the validity of election results; and (3) Juridical, regarding the balance between efficiency and the principle of substantive democracy. The juridical implications of this decision include a change in the electoral system from full concurrent to separated elections, the need for legal harmonization between the Election Law and its implementing regulations, and the formation of a new political cycle (year “X” for the National Pemilu and “X+2” for the National Simultaneous Pilkada). From the regional autonomy perspective, the separation of election timing positively impacts the strengthening of local political identity, increased space for the articulation of regional aspirations, and the opening of opportunities for regional head candidates from smaller or independent parties. Conversely, new challenges also arise, such as increased political and budgetary costs, the potential for political transactions in the nomination process, and policy fragmentation between the central and regional governments. Overall, Constitutional Court Decision No. 135/PUU-XXI/2024 not only affects the technical aspects of election administration but also reconstructs the relationship between the central and regional governments within the context of Indonesia's constitutional democracy. This decision serves as a crucial momentum for lawmakers to rearrange the concurrent election system to better align with the principles of regional autonomy, electoral justice, and government effectiveness.